Implementasi Manajemen Berbasis Sekolah di Pondok Pesantren - Dessi Asdrayany; Dimas Zuhri Ahmad; Anis Zohriah; Machdum Bachtiar (Departement of Mathematics Education, 2023)
This research uses a type of qualitative research with a library research approach by digging up information through the literature regarding leadership and educational institutional management to answer the focus of the study in this study. This study examines the basic concepts of management, the benefits of school-based management, the characteristics of school-based management, the implementation of school-based management, strategies for implementing school-based management, indicators of success of school-based management and the constraints in implementing SBM. Perinsip is one of the important things that must be owned by a leader. The implementation of school management basically chooses the best choice for schools in school development. School-specific management must be sustainable so that in the end it leads to improving education. The characteristics of SBM include the elements of an effective school which are classified into input, process and output